Review on the Different Approach between Alzheimer’s and Parkinson’s Disease - Park, Cheolin; Won, Do-Yeon; Jung, Jae-Eun (Asian Journal of Pharmaceutical Research and Development, 2022)
Alzheimer’s and Parkinson’s disease are disorders which are commonly affects the brain. However, Parkinson’s disease affects the speed of thinking and memory including cognitive functions, whereas Alzheimer’s affects memory and words. With this reviewed article, this information about twodisorders which are very seriously in modern disease will help you prepare for a healthy 100-year-old.